2020
DOI: 10.3389/fmicb.2020.570825
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Modeling for Species-Level Taxonomic Assignment From 16S rRNA: Application to Human Microbiomes

Abstract: With the emergence of next-generation sequencing (NGS) technology, there have been a large number of metagenomic studies that estimated the bacterial composition via 16S ribosomal RNA (16S rRNA) amplicon sequencing. In particular, subsets of the hypervariable regions in 16S rRNA, such as V1–V2 and V3–V4, are targeted using high-throughput sequencing. The sequences from different taxa are assigned to a specific taxon based on the sequence homology. Since such sequences are highly homologous or identical between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…This gene contains nine hypervariable regions (V1–V9) of varying conservation flanked by highly conserved regions. Sequences are highly homologous between species within the same genus, and it is therefore challenging to obtain species resolution by 16S rRNA sequencing [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This gene contains nine hypervariable regions (V1–V9) of varying conservation flanked by highly conserved regions. Sequences are highly homologous between species within the same genus, and it is therefore challenging to obtain species resolution by 16S rRNA sequencing [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we compared several combinations of classification scheme components in the context of the female bladder microbiome to identify bacterial species. This builds on several prior studies comparing databases and classifiers ( 47 49 ), identifiers and databases ( 50 52 ), classifiers and identifiers ( 53 , 54 ), or individual components of the classification scheme for application in microbiome studies. However, to our knowledge, there have been no studies that systematically compared combinations of all the components of a classification scheme (classifiers, databases, and identifiers) for species-level assignment from 16S amplicon experiments.…”
Section: Discussionmentioning
confidence: 99%
“…While database selection is recognized as an important decision in taxonomy assignment for amplicon sequencing studies, few studies have compared the effect of different databases on taxonomy assignment ( 47 , 49 , 55 , 56 ), and none have focused on bladder bacterial species. Park and Won recently compared database performance on mock microbial communities and similarly found that the Silva database outperformed the Greengenes database ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the absent species annotation, we performed 16S rRNA sequencing to profile the OTU level and genus-level abundance of gut bacteria. Moreover, considering inconsistent abundance changes among OTUs assigned as the same species 29,30 , we constructed classifiers using the relative OTUs and genera to capture the most informative taxonomies that could effectively distinguish CRC patients from healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…We formalized the task of CRC or adenoma prediction as a classification problem and focused on operational classification units (OTUs). By using OTUs instead of taxonomic annotations as features, the problem that the same OTU may be inconsistently annotated when using different reference databases was avoided 29,30 .…”
Section: /31mentioning
confidence: 99%